2020
DOI: 10.1108/bjm-07-2019-0274
|View full text |Cite
|
Sign up to set email alerts
|

Are jacks-of-all-trades successful entrepreneurs? Revisiting Lazear's theory of entrepreneurship

Abstract: PurposeThe purpose of this paper is to identify human capital factors that pertain both to setting up and successfully running a business. To achieve this objective, the authors apply and extend the theory of career choice offered by Lazear (2005) that explains individual selection into entrepreneurship.Design/methodology/approachThe authors hypothesise that individuals with broader educational and professional backgrounds are more likely to start a business and are more likely to run a business in the long te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…, 2015; Blumberg and Pfann, 2016; Edelman et al. , 2016; Sahasranamam and Nandakumar, 2020; Kurczewska and Mackiewicz, 2020), but there is little literature exploring and tracing the origin of these individual capital. This paper puts forward an integrated concept of “individual entrepreneurial capital” and defines it as a capital element that includes social, human and financial capital that is conducive to individuals pursuing potential entrepreneurial opportunities, which helps to deepen the understanding of the impact of household on entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…, 2015; Blumberg and Pfann, 2016; Edelman et al. , 2016; Sahasranamam and Nandakumar, 2020; Kurczewska and Mackiewicz, 2020), but there is little literature exploring and tracing the origin of these individual capital. This paper puts forward an integrated concept of “individual entrepreneurial capital” and defines it as a capital element that includes social, human and financial capital that is conducive to individuals pursuing potential entrepreneurial opportunities, which helps to deepen the understanding of the impact of household on entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Reis et al (2021) describes this problematics well, as they identified up to 98 entrepreneurial competencies used in prior research. The problem is not simplified by the fact that entrepreneurship is associated with more diverse educational and professional backgrounds (Kurczewska and Mackiewicz, 2020). Lilleväli and Täks (2017) note that views on entrepreneurial competencies also vary according to the view taken on entrepreneurship education: a narrow approach focuses on entrepreneurship as business creation and management whereas the broad approach targets development and support of an entrepreneurial mindset, enabling value creation in different fields of life.…”
Section: Entrepreneurial Competenciesmentioning
confidence: 99%
“…As Laffineur et al. (2020) state, career hardships and a lack of self-fulfilment drive workers towards entrepreneurship.Diverse work experiences will lead to an increase in willingness to start a business (Astebro and Thompson, 2011; Astebro and Yong, 2016; Kurczewska and Mackiewicz, 2020) because the breadth of functional work experience will favour the generation of new business ideas (Gabrielsson and Politis, 2012; Chen and Thompson, 2016). Krieger et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%